A new high-voltage H2S single noxious gas reliability test for power modules. (September 2019) - Wassermann, T.N.; Schilling, O.; Müller, K.; Rossin, A.; Uhlig, J.
Abstract: The impact of H2 S on the corrosion of Cu electrodes under applied bias is investigated for a test structure that simulates the conditions in a power module. Growth of Cu sulphide dendrites is identified as the predominant aging mechanism, and the influence of the main impact parameters such as humidity, concentration and voltage is modelled. The concept of reactivity monitoring of Cu coupons is applied to a proposed test condition, and the acceleration compared to a standardized operational condition is explained.